Predictors of Depression in Caucasian Patients with Amyotrophic Lateral Sclerosis in Romania - Anca, Motataianu (Brain Sci, 2020)
Depression remains an underdiagnosed comorbidity which significantly decreases the quality of life in amyotrophic lateral sclerosis (ALS) patients. We aimed to investigate the prevalence of depression in a cohort of ALS patients with more than one year of disease evolution. A total of 50 ALS patients were evaluated with the Beck Depression Inventory II (BDI-II) and cognition, using the Mini-Cog Standardized Instrument (MCSI). The clinical disability was evaluated using the ALS Functional Rating Scale (ALSFRS). The prevalence of depression was 42.8%. A lower BDI-II score was significantly correlated with a higher education level, the spouse as a caregiver, spiritual devotion, and employment status (p < 0.05). A multiple linear regression analysis between the BDI-II score as the dependent variable and various independent variables such as spirituality, caregiver status, educational level, and occupational status revealed that only the type of caregiver (spouse or parent/child) significantly affected the BDI-II total score (p = 0.006). The functional disability significantly correlated with loss of appetite and loss of libido (p < 0.001). A high education, spiritual devotion, high ALSFRS, and the presence of the spouse as the caregiver were associated with the absence of depression.